Molecular markers in improvement of Capsicum spp. – a review - Mathew, Deepu (Journal of Spices and Aromatic Crops, 2006)
Use of various molecular markers in improvement of Capsicum spp. including genetic diver-sity analysis, fingerprinting, mapping the genes of interest with special reference to pun-gency and stress resistance, seed purity analysis, phylogenetic studies, genomic library con-struction and linkage analysis has been well demonstrated. This paper reviews the advance-ment and information available on the use of RAPD, RFLP, AFLP, ISSR, SPAR, CAPS andSCAR markers in crop improvement programmes in Capsicum spp.